2020
DOI: 10.1177/0022146520939514
|View full text |Cite
|
Sign up to set email alerts
|

What Is Driving the Drug Overdose Epidemic in the United States?

Abstract: The demand-side perspective argues that the drug overdose epidemic is a consequence of changes in the economy that leave behind working-class people who lack a college education. In contrast, the supply-side perspective maintains that the epidemic is primarily due to changes in the licit and illicit drug environment, whereas a third, distinct perspective argues that income inequality is likely a key driver of the epidemic. To evaluate these competing perspectives, we use a two-level random intercept model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
(109 reference statements)
1
10
0
Order By: Relevance
“…We also find some evidence of a long-run negative effect of inequality, and we investigated if income inequality moderates the relationship between emissions and life expectancy. Consistent with the results of prior research (Chetty et al 2016; Hill et al 2019; Kaplan et al 1996; Thombs et al 2020), in two of three models we find that the effect of GHG on life expectancy becomes more negative as income inequality increases. However, these findings are somewhat inconsistent across the analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also find some evidence of a long-run negative effect of inequality, and we investigated if income inequality moderates the relationship between emissions and life expectancy. Consistent with the results of prior research (Chetty et al 2016; Hill et al 2019; Kaplan et al 1996; Thombs et al 2020), in two of three models we find that the effect of GHG on life expectancy becomes more negative as income inequality increases. However, these findings are somewhat inconsistent across the analysis.…”
Section: Discussionsupporting
confidence: 91%
“…A related body of research reveals direct associations between income inequality and worsened population health outcomes (e.g., Anderson, Bjorklund, and Rambotti 2019; Mishra and Carleton 2015; Pickett and Wilkinson 2015), including reduced life expectancy (e.g., Chetty et al 2016; Hill and Jorgenson 2018; Thombs et al 2020). Inequality directly affects population health because relative deprivation in living standards is associated with lower social-emotional outcomes, maladaptive coping mechanisms, and lower subjective well-being (Oishi, Kesebir, and Diener 2011; Payne, Brown-Iannuzzi, and Hannay 2017; Wilkinson and Pickett 2010).…”
Section: Ghg Emissions Income Inequality and Human Well-being In The United Statesmentioning
confidence: 99%
“…There is some evidence at the community or county level that changes in unemployment and financial resources link economic recessions to increased suicide and drug poisoning rates (Chang et al 2013; dos Santos et al 2016; Gunnell and Chang 2016; Haw et al 2015; Hodwitz and Frey 2016; Thombs et al 2020). Even short-term economic changes can have a long-term impact on individuals’ social status, financial resources, and mental and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Although one study found that deaths by suicide and drug poisoning are concentrated in areas with high economic distress (Monnat 2018), another focusing on areas with high industrialization that were more vulnerable to shocks to economic opportunities in blue-collar occupations found the opposite; suicide and drug poisoning mortality was lower in the more vulnerable areas (Bound et al 2018). Indeed, the processes involved in access to means for self-inflicted deaths, the labor market, and inequality are complex; individual-level positions within their communities are important to consider (Peters et al 2020; Pickett and Wilkinson 2015; Thombs et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation